On the accuracy and precision of numerical waveforms: effect of waveform extraction methodology. (14th July 2016) - Chu, Tony; Fong, Heather; Kumar, Prayush; Pfeiffer, Harald P; Boyle, Michael; Hemberger, Daniel A; Kidder, Lawrence E; Scheel, Mark A; Szilagyi, Bela
Abstract: We present a new set of 95 numerical relativity simulations of non-precessing binary black holes (BBHs). The simulations sample comprehensively both black-hole spins up to spin magnitude of 0.9, and cover mass ratios 1–3. The simulations cover on average 24 inspiral orbits, plus merger and ringdown, with low initial orbital eccentricities e < 10 − 4 . A subset of the simulations extends the coverage of non-spinning BBHs up to mass ratio q = 10. Gravitational waveforms at asymptotic infinity are computed with two independent techniques: extrapolation and Cauchy characteristic extraction. An error analysis based on noise-weighted inner products is performed. We find that numerical truncation error, error due to gravitational wave extraction, and errors due to the Fourier transformation of signals with finite length of the numerical waveforms are of similar magnitude, with gravitational wave extraction errors dominating at noise-weighted mismatches of ∼ 3 × 10 − 4 . This set of waveforms will serve to validate and improve aligned-spin waveform models for gravitational wave science.